Cyber Attacks in the Context of the Pandemic Covid-19 - Virgolici , Ionel Vladimir; Ionita, Alina Melania; Draganescu , Alexandru Drăgănescu; Stegaroiu, Ionel Catalin (Journal of Danubian Studies and Research, 2022)
Information plays a crucial role in maintaining interpersonal relationships and developing society. The use of information technologies has caused rapid change in our society. Although society bears the negative consequences of cybercrime, technology is still used in a wide variety of fields. This proves that it is, in fact, indispensable. To limit cybercrime, states should continue to develop computer technology and create legislation to criminalize harmful acts committed through technology. It is also necessary that the people involved in the fight against this phenomenon receive the necessary training. It is, at the same time, important that the population is well-informed regarding the security of IT systems, thus providing an effective barrier against IT crime.